Identification of cardiac myofilament protein isoforms using multiple mass spectrometry based approaches. Issue 7 (August 2014) - Kooij, Viola; Venkatraman, Vidya; Kirk, Jonathan A.; Ubaida‐Mohien, Ceereena; Graham, David R.; Faber, Matthijs J.; Van Eyk, Jennifer E.; Ge, Ying; Van Eyk, Jennifer
<x xml:space="preserve">Abstract</x> Purpose The identification of protein isoforms in complex biological samples is challenging. We, therefore, used an MS approach to unambiguously identify cardiac myofilament protein isoforms based on the observation of a tryptic peptide consisting of a sequence unique to a particular isoform. Experimental design Three different workflows were used to isolate and fractionate rat cardiac myofilament subproteomes. All fractions were analyzed on an LTQ‐Orbitrap MS, proteins were identified using various search engines (MASCOT, X!Tandem, X!Tandem Kscore, and OMSSA) with results combined via PepArML Meta‐Search engine, and a postsearch analysis was performed by MASPECTRAS. All MS data have been deposited in the ProteomeXchange with identifier PXD000874 (http://proteomecentral.proteomexchange.org/dataset/PXD000874). Results The combination of multiple workflows and search engines resulted in a larger number of nonredundant proteins identified than with individual methods. A total of 102 myofilament annotated proteins were observed overlapping in two or three of the workflows. Literature search for myofilament presence with manual validation of the MS spectra was carried out for unambiguous identification: ten cardiac myofilament and 17 cardiac myofilament‐associated proteins were identified with 39 isoforms and subisoforms. Conclusion and clinical relevance We have identified multiple isoforms of myofilament proteins that are present in cardiac tissue using unique tryptic peptides. Changes in distribution of these protein isoforms under pathological conditions could ultimately allow for clinical diagnostics or as therapeutic targets.